KEPATUHAN TERHADAP KODE ETIK NOTARIS SEBAGAI FONDASI PROFESIONALISME DAN KUNCI KEPERCAYAAN PUBLIK - Nafa Chisbiyah; Dai Putra Fatkhulloh (CV. KAMPUS AKADEMIK PUBLISING, 2025)
A notary is a public official who is trusted by the public to make authentic deeds. In carrying out his duties as a notary legal profession, a notary must uphold legal ethics, dignity, and the nobility of his position. If this is ignored, it can cause losses to the parties and the notary himself. The notary code of ethics includes, notary personality ethics, ethics in carrying out duties and positions, service ethics, ethics among colleagues and the duties and authorities of the supervisory institution in the notary. The code of ethics contains important elements regarding obligations, prohibitions, exceptions and sanctions that will be imposed on notaries who violate the code of ethics. The purpose of the notary code of ethics is to maintain the honor and nobility of the notary profession. This study explores compliance with the notary code of ethics as a foundation of professionalism to increase public trust.